Evaluasi Kesesuaian Lahan Untuk Tanaman Ubi Kayu (Manihot esculenta crant) di Desa Petuaran Hilir Kecamatan Pegajahan Kab. Serdang Bedagai - Antonius Juswanto; Bintang Sitorus; M. M. B. Damanik (Universitas Sumatera Utara, 2014)
The purpose of the study was to find out the land suitability classes in Petuaran Hilir villagePegajahan sub district Serdang Bedagai Regency for cassava. Obtained by 2 SPT (set of land) whatis determined by pursuant to map of land and ground type, map of inclination of slope fromtopography map with the scale 1 : 5000, is later conducted by overlay. Assessment of landsuitability pursuant to staff criterion center the research of land of bogor (1993) using landevaluation method with comparing (matching). The result of analysis showed the unity of allthe sample has appropriate class of land actual at set of land (SPT) 1 is S3(nr) and class of landpotential is S2 (rc). Class of land The actual and suitability classes Soil Map Unit (SPT)2 is S2(wa,rc, nr, er) and potential and suitability classS2(rc).Keywords:suitability of land, Cassava,Petuaran hilir village